Causal effect of waist-to-hip ratio on non-alcoholic fatty liver disease: a mendelian randomization study - Shihao Wu; Yuhong He; Jiaxing Li; Sijie Wang (Frontiers in Genetics)
ObjectiveThis study aimed to explore the potential causal association between waist-to-hip ratio (WHR) and the risk of non-alcoholic fatty liver disease (NAFLD) via the Mendelian randomization (MR) approach.MethodsGenetic variation data pertaining to WHR served as instrumental variables, while genome-wide association study data for NAFLD constituted the outcome event. Primarily, the random-effects inverse-variance weighted (IVW) method was utilized, supplemented by MR Egger, weighted median, simple mode, and weighted mode analyses. Sensitivity analysis entailed the “leave-one-out” approach, with the IVW results forming the foundational basis for this study.ResultsThis analysis included a total of 28 valid single nucleotide polymorphisms (SNPs). IVW analysis indicated an increased risk of NAFLD associated with WHR (OR = 1.61; 95% CI: 1.08–2.41; P = 0.02). Furthermore, MR-Egger regression analysis revealed the absence of horizontal pleiotropy among the included SNPs, albeit with some sample heterogeneity. Lastly, the “leave-one-out” sensitivity analysis demonstrated that no individual SNP significantly influenced the estimated causal association.ConclusionThis study furnishes indicative evidence of a causal link between waist-to-hip ratio and the risk of NAFLD occurrence.